Dynamic modeling and analysis of a novel offshore gangway with 3UPU/UP-RRP series-parallel hybrid structure. (15th December 2022) - Niu, Anqi; Wang, Shenghai; Sun, Yuqing; Qiu, Jianchao; Qiu, Weihan; Chen, Haiquan
Abstract: It is inevitable that the 6-DOF motions of ships at sea will be induced by the marine environmental disturbances. Even though some ships are equipped with mooring or dynamic positioning systems, they still have three-dimensional motions including roll, pitch and heave, which not only reduces the efficiency of people and cargo transfer but also seriously threatens the safety of offshore transshipment. Most offshore gangways use six degrees of freedom Stewart parallel platform to compensate for these ship motions, which is a bit wasteful in both mechanical structure and power consumption. A novel 3UPU/UP-RRP series-parallel hybrid structure offshore gangway is designed in this paper. It is composed of a parallel platform of 3UPU/UP structure and a series transfer gangway of RRP structure. And a compensation scheme is proposed to compensate the roll and pitch motions of the ship with the parallel platform and the heave motion of the ship with the transfer gangway. The dynamic model of the offshore gangway is built by virtual working principle and Newton-Euler method. First, the velocity and acceleration of each component of the parallel platform are derived by vector method. Next, the dynamic model of the parallel platform is obtained by the principle of virtual work. Then, the dynamic model of the serial gangway is established by Newton-Euler method. After that, the accuracy of the dynamic mathematical model was verified by the simulation model. The power consumption of the proposed compensation method is compared with another common compensation method under sinusoidal motion excitation, and it is obtained that this compensation method has lower power consumption. Highlights: A novel 3-UPU/UP-RRP offshore gangway with a series-parallel hybrid structure is proposed. The virtual work principle is used to solve the problem of constraint couple forces inside the 3-DOF parallel structure. The dynamic model of the series-parallel hybrid structure is first established systematically in non-inertial frames. The accuracy of the Matlab dynamic-mathematical model is verified by Adams simulation model. A new compensation method for ship motion is proposed. This method consumes less power than another compensation method.